The impact of gender differences on mortality in elderly patients after hip fracture - Prodović, Tanja T; Ristić, Branko M.; Vučetić, Dušan D.; Ignjatović Ristić, Dragana I. (Vojnosanitetski pregled, 2020)
Background/Aim. Hip fracture is one of the leading causes of death in elderly population. We evaluated the impact of gender differences on mortality rate in elderly patients with hip fracture. Methods. The study included all hospitalized elderly patients (aged over 65 years) with hip fracture during 2013. The patients were classified into four risk groups in accordance with institutional Şişli Etfal risk factor assessment scale ISERFAS to estimate postoperative mortality. Clinical, laboratory and risk score results were gender matched between survived and deceased patients. Hospital mortality was monitored as well as mortality at intervals of three and six months. The prediction effect of gender and overall risk variables on mortality rate were determined by univariate and multivariate logistic regression analyses. Results. The complete sample included 434 female and 163 male patients. Average age of men was 77.95 years and 79.18 years for women. Femoral neck fracture was more often seen in women (44.5%), but with no statistically significant difference (p = 0.57). Significant difference between the genders in relation to the risk score values was determined (p = 0.024). It was observed that the values of risk score was lower in the female patients and higher in the male patients. Cumulative mortality was 6% during hospital stay, 17.8% after three months and 25% after six months, respectively. In-hospital and six months after the hip fracture, the mortality rates were similar in both genders. The mortality rate was significantly higher in male patients (p = 0.035) three months after the hip fracture. The overall risk observed at all mortality intervals was a significant predictor by itself (p = 0.000). Independent gender prediction effect disappeared in joint effects of patients’ overall risk. Conclusion. Gender can be defined as a significant mortality predictor in patients with hip fracture. A risk assessment system to estimate postoperative mortality for hip fractures would be helpful in planning treatment for each patient.